Salmonella pathogenicity islands in host specificity, host pathogen-interactions and antibiotics resistance of Salmonella enterica. - Gerlach, Roman; Hensel, Michael (Berliner und Münchener Tierärztliche Wochenschrift, 2007)
Salmonella enterica is a pathogen highly successful in causing a variety of gastrointestinal and systemic diseases in animals and humans. While some serovars of S. enterica are able to infect a broad range of host organisms, other serovars are highly restricted to specific host species. The colonization of hosts by S. enterica depends on the function of a large number of virulence determinants. The molecular analyses of virulence genes demonstrated that most of these loci are clustered within Salmonella Pathogenicity Islands (SPI). SPI1 and SPI2 each encode type III secretion systems (T355) that confer main virulence traits of S. enterica, i.e. invasion, enteropathogenesis and intracellular survival and proliferation. Further SPI encode factors that contribute to intracellular survival, different types of adhesins, or effector proteins of the SPI1-T3SS or SPI2-T3SS. The availability of genome sequences of several serovars of S. enterica also revealed serovar-specific SPI. In this review, the main characteristics of the currently known SPI are summarized with focus on their roles in various animal hosts and putative functions in human infections.